A controlled study of diet in patients with gout. Issue 2 (April 1983) - Gibson, T; Rodgers, A V; Simmonds, H A; Court-Brown, F; Todd, E; Meilton, V
Abstract : To determine whether patients with gout have a diet which is distinctive in quality or quantity a careful dietary questionnaire was posed over 7 days to 61 men with gout and 52 control subjects. The average daily intake of most nutrients, including total purine nitrogen, was similar except that the patients with gout drank significantly more alcohol. Beer was the most popular beverage, and 25 (41%) of those with gout consumed more than 60 g alcohol daily (equivalent to 2 . 5 litres of beer). The heavy drinkers had a significantly higher intake of purine nitrogen, half of which was derived from beer. Though the effect of ingested purine on the blood uric acid is difficult to estimate, it probably was sufficient to have a clinical effect, augmenting the hyperuricaemic effect of alcohol itself.